Amniotic-Umbilical-to-Cerebral Ratio – A Novel Ratio Combining Doppler Parameters and Amniotic Fluid Volume to Predict Adverse Perinatal Outcome in SGA Fetuses At Term - Stumpfe, Florian Matthias; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Emons, Julius; Gass, Paul; Mayr, Andreas; Schmid, Matthias; Beckmann, Matthias Wilhelm; Stelzl, Patrick (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Introduction of a novel ratio – the amniotic-umbilical-to-cerebral ratio (AUCR) – to predict adverse perinatal outcome in SGA fetuses at term and comparison of its predictive accuracy with established parameters.Materials and Methods This retrospective cohort study included 165 singleton pregnancies with SGA fetuses (birth weight < 10th percentile) at term. Cases with planned vaginal delivery and documented pulsatility indices (PI) of the umbilical artery (UA), middle cerebral artery (MCA), and single deepest pocket (SDP) were included. CPR was calculated as the ratio between MCA PI and UA PI, UCR as the ratio between UA PI and MCA PI. AUCR was defined as follows: SDP/(UA PI/MCA PI). Adverse perinatal outcomes were defined as operative intervention (OI), OI due to fetal distress, admission to the neonatal intensive care unit (NICU), and composite adverse perinatal outcome (CAPO). Associations between Doppler parameters and these outcomes were estimated using regression analyses.Results OI was statistically significantly associated with UCR, SDP, and AUCR, whereas no association was observed for UA PI, MCA PI, and CPR. Fetuses requiring OI due to fetal distress revealed a significantly higher UA PI and UCR as well as a lower MCA PI, CPR, and AUCR. With regard to NICU admission and CAPO, a significantly higher UA PI and lower CPR were found. Furthermore, a significant association was shown for SDP, UCR, and AUCR. AUCR achieved the best area under the curve for all outcome parameters.Conclusion AUCR leads to an improvement in the prediction of unfavorable outcome in SGA fetuses at term. Furthermore, results of our study show that UCR might be superior to CPR.
Keywords: SDP; amniotic fluid; CPR; UCR; AUCR